Attitudes toward gender equality in sport among Europeans - Wicker, Pamela; Cunningham, George B. (Frontiers in Psychology, 2025)
IntroductionThis study examines the role of societal, interpersonal, and individual factors in explaining Europeans’ attitudes toward gender equality in sport and the role of interactions between gender, age, and social class.MethodsThe empirical analysis uses survey data from residents in 27 European countries in 2022 (n = 19,396). Respondents’ attitudes toward gender equality in sport are captured by two statements about evenly following female and male sport in the media and the inspirational potential of female role models among managers, athletes, officials, and coaches. Regression analyses are estimated with the attitude variables as outcomes. Societal (gender equality climate in country), interpersonal (sport participation), and individual factors (gender, age, social class; and their interactions) served as independent variables.ResultsThe results show that respondents have higher attitudes toward female role models than toward female sport in the media. A country’s gender equality climate has a negative association with following female sport in the media, but a positive one with female role models. Sport participation is positively associated with female sport in the media. Women score higher on both attitude measures. Older individuals and those from lower social classes evenly follow female sport in the media. Interactions between gender, age, and social class also explain attitudes toward gender equality in sport.DiscussionThis study is innovative as it provides information about how the resident population thinks about gender equality in sport and which factors are relevant for higher or lower attitudes. The European-wide dataset is unique and allows a comprehensive analysis.